Kondisi Sosial Ekonomi dan Mekanisme Pemberdayaan Nelayan Tangkap - Tusana Nurul Safaah; Nunik Mulyandari; Budi Satriyanto; Karyoto Karyoto (Zoologi: Jurnal Ilmu Peternakan, Ilmu Perikanan, Ilmu Kedokteran Hewan, 2024)
The aim to be achieved in this research is to find out the socio-economic status and empowerment of fishing fishermen. The method used to answer the problems in this research is a literature review using secondary data sources. The results of the research show that the social and economic conditions of the capture fishermen group can certainly be seen from the types of fishermen, the first of which is boat charter fishermen, where they have a more stable social and economic status. Second, fishermen in the labor category where these fishermen have the most worrying social and economic status. Third, owner fishermen, where this type of fisherman has good social and economic status. Fourth, entrepreneurs in this mechanism are at the most important social and economic strata. Empowerment that can be carried out is First, the revitalization of ships and fishing gear, which in this case is realized by the government through the formation of groups. Second, empowerment that can be carried out is by providing capital assistance to fishermen where the mechanism for providing assistance can be implemented on a rolling basis using regional money. Third, conduct training for fishermen